Tobacco, occupation and non-transitional-cell carcinoma of the bladder: an international case-control study - Fortuny, Joan; Chang-Claude, Jenny; Wahrendorf, Jürgen (International journal of cancer, 1999)
Transitional-cell carcinoma is the dominant histological type of malignant tumors of the urinary bladder. There is limited information on risk factors for non-transitional-cell carcinoma (NTCC) of the bladder. We used data from 9 case-control studies on bladder cancer from 6 European countries to examine the association between NTCC, tobacco smoking and occupation. Information on 146 cases diagnosed with NTCC were matched by age, gender and study center to 727 non-cancer population or hospital controls and also with 722 transitional-cell-bladder-cancer controls. Lifetime smoking and occupational history were evaluated. A statistically significant excess risk for NTCC was observed for current smoking [odds ratio (OR) = 3.61, 95% confidence interval (CI) 2.08-6.28]. The risk increased with higher tobacco consumption (OR for highest tertile of pack-years = 7.01, 95% CI 3.60-13.66). The risks were higher for squamous-cell carcinomas than for other types of NTCC. Among major occupational groups, a significant excess risk was seen for field-crop and vegetable-farm workers (OR = 2.06, 95% CI 1.03-4.10). These results indicate that NTCC of the bladder is associated with smoking and specific occupations. The risk pattern seems to differ, in part, from that observed for transitional-cell carcinoma of the bladder. Int. J. Cancer 80:44-46, 1999. © 1999 Wiley-Liss, Inc.